Hak paten sebagai objek jaminan fidusia berdasarkan peraturan perundang-undangan mengenai jaminan fidusia dan paten - Herda Mardiana; Muhamad Amirulloh; Pupung Faisal (Jurnal Cakrawala Hukum, 2020)
The issuance of the latest law regarding patent rights is Law Number 13 Year 2016 Regarding Patents which in article 108 paragraph (1) states that Patent Rights can be used as objects of fiduciary security. Fiduciary guarantees of patents will follow the procedures set out in Law Number 42 year 1999 regarding Fiduciary Guarantees. Patents have fulfilled the requirements specified in Article 1 point 2 of the Fiduciary Guarantee Law, but in practice until now the financial institutions in Indonesia have not received patents as objects of fiduciary collateral in filing bank loans. Normative-juridical approach methodsis used in this research, with descriptive-analytical research spesifications aimed at consideringrelation between applicable legislation and theories with the practice of implementation concerning the problems studied. Data technique used in this research is analyzed by using normative-qualitative method. The results of the study state that until now financial institutions in Indonesia have not yet received patents as fiduciary guarantees because peten rights as fiduciary guarantees have not received legal certainty because the formulation of the norms contained in Article 108 paragraph (1) of the Patent Law only regulates and does not compel.How to cite item: Mardiana, H., Amirulloh, M., Faisal, P. (2020). Hak paten sebagai objek jaminan fidusia berdasarkan peraturan perundang-undangan mengenai jaminan fidusia dan paten. Jurnal Cakrawala Hukum, 11(2), 177-186. doi:https://doi.org/10.26905/idjch.v11i2.4094